Navigating Digital Transformation: The Roles of Resilience, Job Security, and Social Support in Shaping Turnover Intention among Indonesian Architects - Altheannisa Agatha Soraya; Niken Ardiyanti (HM Publisher, 2024)
The architectural sector in Indonesia is experiencing rapid digital transformation, introducing both opportunities and challenges for architectural workers. This study examines the impact of this transformation on turnover intention by analyzing the interplay between resilience, job security, social support, and job satisfaction. A cross-sectional survey was conducted among 300 architectural workers in Indonesia. The Covariance-Based Structural Equation Model (CB-SEM) was used to analyze data and assess the direct and indirect effects among the variables. The results showed that resilience positively influenced social support and job satisfaction. Job security also positively affected job satisfaction. However, social support was found to have a positive impact on turnover intention, a finding unique to this context. Both social support and job satisfaction mediated the relationship between resilience and turnover intention, while job satisfaction also mediated the relationship between job security and turnover intention. In conclusion, the study highlights the complex interplay between individual and organizational factors in shaping turnover intention within the Indonesian architectural sector. The findings suggest that promoting resilience and job security, while addressing the potential impact of social support on turnover intention, is crucial for talent retention in this dynamic environment.